2010
DOI: 10.1158/0008-5472.can-10-1307
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Papillomavirus E6 Proteins Must Interact with p300 and Block p53-Mediated Apoptosis for Cellular Immortalization and Tumorigenesis

Abstract: The binding of the papillomavirus E6 protein to E6AP and the induction of p53 degradation are common features of high-risk genital human papillomaviruses (HPV); cutaneous HPVs, on the other hand, lack these capacities. Nevertheless, several cutaneous HPV types of the β-genus, such as HPV38 are associated with tumor formation when combined with genetic predisposition, immunosuppression, or UV exposure. In an animal model system, the cottontail rabbit papillomavirus (CRPV) rapidly induces skin cancer without add… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 48 publications
(74 reference statements)
0
73
0
Order By: Relevance
“…Finally, various publications have reported the interaction of E6 with the acetyltransferases p300 and CBP (23,44,49,71,72). Our comprehensive analysis showed that among the genus alpha E6 proteins, HPV16 E6 is unique in its ability to bind to both CBP and p300 ( Fig.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Finally, various publications have reported the interaction of E6 with the acetyltransferases p300 and CBP (23,44,49,71,72). Our comprehensive analysis showed that among the genus alpha E6 proteins, HPV16 E6 is unique in its ability to bind to both CBP and p300 ( Fig.…”
Section: Resultsmentioning
confidence: 69%
“…E6s from HPV type 16 (HPV16), -18, -11, -5, -8, and -38 as well as those from cottontail rabbit papillomavirus (CRPV) and bovine papillomavirus type 1 (BPV1) have been reported to bind to the acetyltransferases CBP and/or p300, although this has this been demonstrated convincingly only for HPV16, -5, and -8 E6s by a coimmunoprecipitation of endogenous p300 from E6-expressing cells (23,44,49,61,71,72). The downstream effects of the 16E6-p300/CBP interaction have been proposed to include inhibition of p53 and NF-B transcription and an ultimate inhibition of cellular differentiation (49) and a downregulation of p53 activity and p53-dependent transcription (61,71).…”
mentioning
confidence: 99%
“…Mucosal high-risk HPV types induce p53 degradation via the E6 oncoprotein. Although HPV49 has the same mechanism as the mucosal high-risk human papillomavirus types in inactivating p53 (31), other beta HPV types target this cellular tumor suppressor by alternative strategies (3,7,9,14). We previously showed that the expression of HPV38 E6 and E7 oncoproteins in primary keratinocytes promoted accumulation of the p53 antagonist ⌬Np73␣ and cellular immortalization (3,4,6,14).…”
Section: Discussionmentioning
confidence: 99%
“…Beta HPV types were originally isolated in patients suffering from a rare autosomal recessive cancer-prone genetic disorder, epidermodysplasia verruciformis (EV) and are consistently detected in nonmelanoma skin cancers from EV patients and immunocompromised and normal individuals (2). Many independent studies have demonstrated that the E6 and E7 proteins of several HPV types display transforming activities in in vitro and in vivo experimental models (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). We previously showed that E6 and E7 of beta HPV38 are able to efficiently immortalize primary human keratinocytes (4,6).…”
mentioning
confidence: 99%
“…The E6 proteins of several beta papillomavirus types, including HPV5 and 8, target the proapoptotic protein Bak for degradation and thus prevent UV-induced apoptosis (9). They furthermore bind to p300, resulting in inhibition of p53-induced apoptosis (10), reduction of ATR mRNA and protein levels, and finally delayed repair of UV-damaged DNA (11). These activities may result in chromosomal instability particularly in the context of sun exposure and may eventually contribute to cancer development.…”
Section: Introductionmentioning
confidence: 99%